Tracing The Development And Governance Of Zakat In Jordan: A Detailed Historical And Institutional Analysis - Nur, Melanie Azzahra (Universitas Muhammadiyah Sumatera Utara, 2025)
Poverty is a case that has become an unforgettable story throughout the history of human life, one that humanity continues to grapple with. The efforts to eradicate poverty have been a central theme of human development.. Methode is explore the implementation of zakat in Jordan and its impact on poverty alleviation, a comprehensive research methodology was employed. The study began with a historical analysis of zakat practices, tracing its evolution from the classical Islamic period to the present day. The findings of this study reveal a multifaceted approach to zakat implementation in Jordan. Historically, zakat has been an essential component of Jordan’s social welfare system, with its roots tracing back to early Islamic governance. Over time, the system evolved, and modern legislation was introduced to formalize zakat collection and distribution. In contemporary Jordan, zakat is governed by both state-sanctioned institutions and religious organizations, working in tandem to ensure that the funds are channeled effectively to those in need. The Jordanian government has enacted laws that facilitate the collection and distribution of zakat, with the Ministry of Awqaf and Islamic Affairs playing a central role in overseeing zakat activities. This institutionalized approach has ensured that zakat reaches marginalized communities, including refugees and low-income households, helping to reduce poverty levels in these groups